PENERAPAN PROBLEM BASED LEARNING DALAM MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA SMA KELAS X - Indriani, Widya (Universitas Muslim Nusantara Al Washliyah, 2025)
This research is classroom action research which aims to find out an overview of increasing students' ability to understand mathematical concepts by applying the Problem Based Learning (PBL) learning model to exponential number material. The research was conducted at SMA Negeri 14 Medan, specifically in class X-3 for the 2024/2025 academic year, as many as 33 students. The data collection technique used was using interviews, observation and tests of students' understanding of mathematical concepts. The power analysis technique used in this research is all qualitative data, namely observations, interviews and test results on students' understanding of mathematical concepts. The research design used is the Spiral model from Kemmis and Taggart which includes 4 stages in each cycle, namely the planning stage, action stage, observation stage and reflection stage. Based on the results of research that has been carried out, it is found that the Problem Based Learning learning model can improve students' ability to understand mathematical concepts, especially students in class X-3 of SMA Negeri 14 Medan. This is proven by research results which show an increase in the average value of test results from cycle I to cycle II by 35.98% as well as an increase in students' conceptual understanding skills from cycle I to cycle II, namely by 50%.